ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Motor Sport Suzuki Di Kota Semarang) - Maulana S, Ilham; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2017)
Competition in motorcycle sales among motorcycle manufacturers especially motor sport in Indonesia is very tight, one of which Suzuki sport bike sales decreased in 2012-2015, if this continues to happen is not impossible Suzuki will have difficulty to follow the competition with other competitors so that will have an impact on Suzuki's own survival. The purpose of this study to determine the effect of product quality, product innovation and brand trust on purchasing decisions Suzuki motor sport. Samples in this study are consumers who buy and use Suzuki sport bikes in Semarang which amounted to 100 respondents selected by using purposive sampling method. The analytical technique used to process the data in this study using SPSS 20.The results of the analysis in this study indicate that product quality and product innovation have a positive and significant effect on brand trust, then brand trust has a positive and significant effect on purchasing decision. In addition, product quality does not significantly influence purchasing decisions and product innovations have a positive and significant impact on purchasing decisions.